Scientific protocols for fire investigation - Lentini, John J. (Boca Raton, Florida : CRC Press, 2013)
'Providing the critical information necessary to conduct an effective fire investigation, this new edition of a best-selling text includes four new cases and new and expanded discussion of power strips and surge suppressors, space heater fires, source identification, and changes in NFP A 921. Integrating historical, theoretical, and practical aspects in a scientific context, specifically chemistry, physics, and fluid dynamics, it explains the latest lab techniques, ethics codes, mathematical prediction, and forensic reports as well as new graphics showing predicted versus measured phenomena'--
Includes bibliographical references and index.
Keywords: Fire investigation